Poisoning due to acetylcholinesterase inhibitors in the medical emergency unit, Chris Hani Baragwanath Academic Hospital, Soweto, South Africa - Saffy, Patricia Marie (My University, 2017)
Introduction: Acetylcholinesterase Inhibitor (AChEI) poisoning is well described in chemical warfare and is commonly used for attempted suicide in many third world countries. Methods: This study serves to describe the demographic factors, temporal relationships and causes of acetylcholinesterase inhibitor overdose at a tertiary hospital emergency department in Gauteng, South Africa. Cross sectional chart review from the adult emergency unit overdose register was used to extract those patients with AChEI overdose and analysed for demographics, temporal relationships, presenting signs and blood results, treatment regimens and emergency department outcomes. Results: Of the 126 patients with AChEI overdose during this period over threequarters (77%) had taken AChEI for attempted suicide. AChEI were usually taken alone without being mixed with other toxins, medicines or poisons. Males (54.3%) were more likely to attempt AChEI overdose than females. Younger people were more likely to overdose on AChEI with the majority (43.7%) being between 20-29 years, 24.6% between 30-39 years and 17.4% between 14-19 years. The remainder were over 40 years. Miosis was the most common sign of poisoning exhibited by 74% of patients. Emergency treatment was supportive with urgent use of high doses of atropine in escalating doses. Oximes and benzodiazepines were not used in the initial urgent treatment. Most patients (69%) were admitted to a high care, nonventilated ward for observation and ongoing treatment but 19% of patients were severe enough to be ventilated and admitted into ICU. A small percentage, (12%) were sent to general wards. The mortality from AChEI poisoning in the unit was 2.4%. Conclusion: Typically, young healthy people were found to abuse AChEIs; the majority of which had suicidal intent. An average of 5 patients presented with AChEI poisoning per week. The mortality rate in the unit was very low.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment for the degree of Master of Science in Medicine in Emergency Medicine. Johannesburg 2017.
Keywords: Cholinesterase Inhibitors (Acetylcholinesterase Inhibitor); Emergency Service, Hospital